2014
DOI: 10.1260/1747-9541.9.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of External and Internal Attention Focus Training on Foot-Strike Patterns in Running

Abstract: The provision of instructions is an important task constraint when altering movement behaviours. Using instructions as a form of task constraint could be an effective approach to help learners improve their performances. Specifically, changing running gait from a heel to forefoot strike pattern can reduce incidences of injuries. By providing different attentional instructions, external and internal focus instructions, which emphasise movement effect and movement form respectively, can be used to alter foot str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The primary reason for exclusion on obtainment of full text was inadequate participant numbers (ie, less than 10 participants per group), and included six studies on step rate manipulation,34–38 five studies on strike pattern comparison36 39–42 including one in a PFP population,41 one study on step width manipulation,43 one study on cues to reduce hip adduction,44 two studies on reducing impact loading variables45 46 and three combination studies 40 47–49. Additional reasons for exclusion included one combination study for absence of clinical or biomechanical analysis,50 one combination study for including transition to minimalist footwear during gait retraining,51 two step rate manipulation studies52 53 for absence of statistical comparison of biomechanical differences and one step rate manipulation study54 which combined hill running.…”
Section: Resultsmentioning
confidence: 99%
“…The primary reason for exclusion on obtainment of full text was inadequate participant numbers (ie, less than 10 participants per group), and included six studies on step rate manipulation,34–38 five studies on strike pattern comparison36 39–42 including one in a PFP population,41 one study on step width manipulation,43 one study on cues to reduce hip adduction,44 two studies on reducing impact loading variables45 46 and three combination studies 40 47–49. Additional reasons for exclusion included one combination study for absence of clinical or biomechanical analysis,50 one combination study for including transition to minimalist footwear during gait retraining,51 two step rate manipulation studies52 53 for absence of statistical comparison of biomechanical differences and one step rate manipulation study54 which combined hill running.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies that have examined gait retraining have attempted to use verbal instructions that manipulate participants’ attentional focus. In line with Wulf's model, Chow, Woo, and Koh predicted that an external focus of attention would facilitate a more effective transition from a rearfoot strike to forefoot strike pattern. Chow et al found that both types of instruction were beneficial in modifying foot strike patterns.…”
Section: Introductionmentioning
confidence: 82%
“…Chow et al found that both types of instruction were beneficial in modifying foot strike patterns. However, Chow et al’s external focus cue was problematic in that they asked participants in this condition to “Strike your foot” in line with a virtual line that was projected onto the treadmill. The use of the word “foot” may well have engendered at least a partial internal focus, confounding their results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a general cognitive capacity, attention has been widely studied regarding to motor learning and motor control, researchers have concluded that attentional focus plays a key role on motor performance (Chow, Woo, & Kon, 2014;Wulf, 2013). Studies have tried to answer one of the big issues related to the endurance sport field, where to focus attention to perform at one's best?…”
Section: Runningmentioning
confidence: 99%